Transparency and Accountability in Report Management - Sandy, Khairum Nadila; Haliah, Haliah; Nirwana , Nirwana (Lembaga Riset Ilmiah, 2025)
The aim of this study is to provide a comprehensive context on the importance of transparency and accountability in financial management, and to provide knowledge that will help improve the financial management systems of organizations and the government sector. This research uses a literature method, an approach that aims to analyze and integrate various literature related to the issues discussed. This study uses English or Indonesian articles published in the last 5 years (2021-2025). From the 18 journals studied, it is shown that transparency and accountability in financial statements are very important elements that help increase trust, prevent fraud, and facilitate good decision-making. The study observed that organizations that do not apply these principles risk facing a crisis of trust and legal sanctions, and can increase the risk of bankruptcy Transparent and accountable financial management contributes to organizational stability and operational efficiency